2004
DOI: 10.1177/0272431603262667
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Maternal and Early Adolescent Attitudes Toward Children’s Nurturance and Self-Determination Rights

Abstract: Children’s rights to nurturance and self-determination have been included in social policy agendas for many years. Children’s and parents’ attitudes concerning children’s rights are likely an important determinant of whether rights on paper actually serve to protect the well-being of children, yet there is little research on factors associated with support for children’s rights. This study examined maternal (parenting style, sociopolitical attitudes) and child (emotional autonomy, role in family decision makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
94
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(113 citation statements)
references
References 32 publications
12
94
6
1
Order By: Relevance
“…These two variables share about 12% of the variance, which is not negligible given the complexity and the multiple determination of the self-esteem construct. The finding that children who report higher participation rights fulfillment also report higher self-esteem corresponds with claims and empirical findings in the literature on the association between participation in family decision-making and self-esteem (Malone & Hartung, 2010;Persson et al, 2007).…”
Section: Perceptions Of a Democratic Climate In The Familysupporting
confidence: 84%
See 1 more Smart Citation
“…These two variables share about 12% of the variance, which is not negligible given the complexity and the multiple determination of the self-esteem construct. The finding that children who report higher participation rights fulfillment also report higher self-esteem corresponds with claims and empirical findings in the literature on the association between participation in family decision-making and self-esteem (Malone & Hartung, 2010;Persson et al, 2007).…”
Section: Perceptions Of a Democratic Climate In The Familysupporting
confidence: 84%
“…parents' willingness to listen to and consider the views of adolescents. In a separate analysis, the adjustment of youth from families characterized by high youth influence on family matters was compared to the adjustment of youth from families less open to youths' influence (Persson et al, 2007). The results showed that adolescents from families open to adolescent influence had the lowest scores on measures of delinquency, alcohol consumption, depression and expectation of failure, and the highest scores on measures of self-esteem.…”
mentioning
confidence: 99%
“…This has demonstrated the role played by parental attitudes and beliefs, and parenting styles in determining children's involvement in choice-making (Peterson-Badali et al, 2004;Pyke-Grimm et al, 2006;Jackson et al, 2008;Mack et al, 2011;Coyne, 2008;Lease & Dahlbeck, 2009;Commendador, 2010).…”
Section: Choice-making In Familiesmentioning
confidence: 99%
“…As a matter of fact, it is likely that there will be a conflict if there are discrepancies between what the children have learned at the school and the house. In addition, children's using their right to participation in the family supports their self-determination skills (Peterson-Badali, Morine, Ruck, & Slonim, 2004;Day, Peterson-Badali, & Ruck, 2006). On the other hand, the family (Brown, Cohen, Johnson, & Salzinger, 1998), which is among the risk factors for child abuse and neglect, can expose the children to emotional abuse with humiliating comments, even if they provide the child adequate care, protection and education (Horton & Cruise, 2001).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%